One Step Forwards, Two Steps Back: Women's Rights 20 Years after the Good Friday Agreement. Issue 2 (31st August 2017) - Pierson, Claire
Abstract: Despite the relatively unusual (by global standards) involvement of women in negotiations to the Good Friday Agreement (GFA), it is generally recognised that gender has been marginalised both in the descriptive and substantive representation of women in conflict transformation. Twenty years after the Agreement, this article discusses and reflects on the implications of the exclusion of gender policy issues both for women and wider society. Within the agreement itself women are only briefly mentioned with regard to political participation, and the institutional structures created from the GFA through their very design deprioritise any identity cleavage which is not ethno-national. In addition to impacting on the representation of women in formal politics, gendered issues such as gender-based violence either become sectarianised or marginalised, but ultimately remain unresolved. The article addresses the potential for developing and creating gender-sensitive policy concluding that processes of civic engagement and mobilisation offer increasing potential to disrupt the limitations of the overarching macro-political institutional structures.